Auditory Stimulus Timing Influences Perceived duration of Co-Occurring Visual Stimuli - Romei, Vincenzo; De Haas, Benjamin; Mok, Robert M.; Driver, Jon (Frontiers in Psychology, 2011)
There is increasing interest in multisensory influences upon sensory-specific judgements, such as when auditory stimuli affect visual perception. Here we studied whether the duration of an auditory event can objectively affect the perceived duration of a co-occurring visual event. On each trial, participants were presented with a pair of successive flashes and had to judge whether the first or second was longer. Two beeps were presented with the flashes. The order of short and long stimuli could be the same across audition and vision (audiovisual congruent) or reversed, so that the longer flash was accompanied by the shorter beep and vice versa (audiovisual incongruent); or the two beeps could have the same duration as each other. Beeps and flashes could onset synchronously or asynchronously. In a further control experiment, the beep durations were much longer (tripled) than the flashes. Results showed that visual duration-discrimination sensitivity (d') was significantly higher for congruent (and significantly lower for incongruent) audiovisual synchronous combinations, relative to the visual only presentation. This effect was abolished when auditory and visual stimuli were presented asynchronously, or when sound durations tripled those of flashes. We conclude that the temporal properties of co-occurring auditory stimuli influence the perceived duration of visual stimuli and that this can reflect genuine changes in visual sensitivity rather than mere response bias.